The Effect of Good Corporate Governance on Financial Performance - Antaiwan Bowo Pranogyo; Junaidi Hendro; Nia P. Simanjuntak (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
The reason for this experimentation is to decide the consequence of proper agency governance on the financial standard overall accomplishment and feasibility of meals and beverage corporations indexed on the Indonesia stock trade (BEI) from 2015 to 2019. This finds out about hired quantitative studies to approach with linear regression analysis of panel data using SPSS 23 as the data analysis technique. This study's population protected all food and beverage groups indexed on the Indonesia inventory exchange between 2015 and 2019. To attain a sample of 20 organizations, the pattern was decided using the purposive sampling approach. The records series approach makes use of documentation received from the legitimate IDX website, www.idx.co.id. The outcomes of this discovery approximately finish that: (1) The unbiased board of commissioners and the audit committee have a giant impact on economic performance; however, the board of administrators has no big impact on monetary overall performance, based on the outcomes of a linear regression evaluation of panel records with a price stage of 5%. (2) it is possible to use a regression version to explain financial realization with the impartial board of commissioners, board of directors, and audit committee.